Wspieranie dochodów polskich rolników przez dopłaty bezpośrednie po przystąpieniu Polski do Unii Europejskiej - Lech, Aleksandra (Zeszyty Wiejskie, 2014)
The article aims to present an analysis of direct payments system with a special focus on the influence this instrument of the Common Agricultural Policy had on income situation of Polish farms between 2004–2012. Apart from single area payments the system of direct payments consists of separate payments and special support as well as Complementary Area Payments that are totally financed from national sources. Undoubtedly, an increase of direct payments for Polish farmers from PLN 6,7 billion in 2004 to 14 billion in 2013 was a crucial factor in improving income situation of farms. An average disposable monthly income per one farm increased from PLN 2595.44 in 2004 to 4749.75 in 2012, whereas an average monthly income per one person in a farm rose from PLN 735 to 1091.55.